2005
DOI: 10.1677/joe.1.06277
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of the thyroid-stimulating hormone receptor gene in feline hyperthyroidism: parallels with human hyperthyroidism

Abstract: Hyperthyroidism is the most common endocrinopathy in cats, and is both clinically and histopathologically very similar to human toxic nodular goitre (TNG). Molecular studies on human TNG have revealed the presence of mis-sense mutations in the thyroid-stimulating hormone receptor (TSHR) gene, most frequently in exon 10. Our hypothesis was that similar mutations exist in hyperthyroid cats. Genomic DNA was extracted from 134 hyperplastic/ adenomatous nodules (from 50 hyperthyroid cats), and analysed for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
(121 reference statements)
0
22
0
1
Order By: Relevance
“…Not all nodules taken from an individual cat or thyroid lobe showed the same mutations, with different mutations appearing in different adenomas and hyperplastic nodules (Watson et al 2005). A similar scenario has been found in human hyperthyroidism (Fuhrer et al 1996, Holzapfel et al 1997, Tonacchera et al 1998.…”
Section: Figurementioning
confidence: 59%
See 2 more Smart Citations
“…Not all nodules taken from an individual cat or thyroid lobe showed the same mutations, with different mutations appearing in different adenomas and hyperplastic nodules (Watson et al 2005). A similar scenario has been found in human hyperthyroidism (Fuhrer et al 1996, Holzapfel et al 1997, Tonacchera et al 1998.…”
Section: Figurementioning
confidence: 59%
“…In hyperthyroid cats, early studies carried out in small numbers of cats failed to identify any TSHR mutations (Pearce et al 1997, Peeters et al 2002. However, a later detailed study of 134 nodules from 50 hyperthyroid cats found ten missense mutations, of which five have previously been associated with human hyperthyroidism (Watson et al 2005). The most common TSHR mutation detected in cats is Met452-Thr (a substitution of methionine by threonine), which is analogous to the human mutation Met453-Thr observed in sporadic human nodular goiter , Nishihara et al 2009).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In 96% of cases, feline hyperthyroidism is associated with a unilateral or bilateral nodular goiter caused by true adenomas or nodular hyperplasia of the thyroid, and these histopathological changes are similar to those found in human toxic nodular goiter (6,7). Although early work failed to find TSH receptor mutations in relatively small numbers of feline hyperthyroid glands (*n ¼ 10) (8,9), a detailed study of 134 nodules from 50 hyperthyroid cats found 10 missense mutations of which 5 have previously been associated with human hyperthyroidism (10). In addition, altered expression of inhibitory and stimulatory Gproteins has been found in hyperthyroid cats (8,11).…”
Section: Introductionmentioning
confidence: 81%
“…Thereafter, several groups reported 4 TSHR mutations (Met453Thr, Ile486Met, Leu512Arg, and Table 4. Clinical characteristics in patients without TSHR and Gsα mutations in AFTN due is the most common (34%) TSHR mutation [27]. Several studies of human AFTN also observed a relatively high prevalence of Met453Thr, which was not explained by iodine intake [10,15].…”
Section: Analysis Of Thyroid Functionmentioning
confidence: 98%